Characterization of three maca (Lepidium peruvianum G. Chacon) echotypes’ total proteins by unidimensional y bidimensional electrophoresis - Monteghirfo, Mario (2007)
Objective: To characterize soluble proteins present in Lepidium peruvianum G. Chacon ‘maca’ root by both unidimensional and bidimensional electrophoresis. Design: Observational and cross-sectional type study. Setting: Alberto Guzman Barron Biochemistry and Nutrition Research Center, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Materials: Roots of Lepidium peruvianum G. Chacon ‘maca’ white, yellow and purple ecotypes, collected in Junin and obtained from Universidad Nacional del Centro del Peru. Methods: Soluble total proteins extraction with an antioxidant solution and characterization by both unidimensional and bidimensional electrophoresis were done. Main outcome measures: Soluble protein number, molecular weight and most abundant proteins’ isoelectrical points. Results: The unidimensional electrophoretic analysis showed predominance of two proteins (72% of total soluble proteins): one with 22,5 kDa denominated in the present work as “macatina” (51% of the total protein) and another with 17,0 kDa (21% of total soluble protein). The bidimensional electrophoretic map sample showed that both ‘macatina’ and the 17,0 kDa protein are basic and display three charge isomers distributed in an isoelectric point (pI) ranging from 7,1 to 8,2. Conclusions: The soluble proteins ecotypes studied showed a complex electrophoretical pattern, being macatina the most abundant protein.